MEASURING THE STROKE OF CONE DISK SPRINGS IN POWER ACCUMULATORS OF THE TURBOGENERATOR STATOR CORE USING A CAPACITIVE SENSOR - A. S. Levytskyi; I. O. Zaitsev; K. O. Kobzar (Приборы и методы измерений, 2018)
The troubleproof and efficient work of powerful turbogenerators depends on the stability of their main mechanical parameters, which include the stator core pressing. The aim of the work was to describe the possibility of using a multielement capacitive sensor with coplanar electrodes to measure the movement of disk springs of the stabilizer systems power batteries in the turbogenerator stator core.The state of the core pressurizer can be indirectly assessed by measuring the displacement of the disk springs in power accumulators, which are installed on the tightening prism of the core instead of the compression nuts. To measure the movement of springs, a coplanar capacitive sensor with sectoral electrodes built into the power accumulators design is proposed. Each sector contains its own elementary sensor formed by coplanar electrodes. Each elementary sensor in each sector is placed on an annular dielectric plate and is formed by coplanar electrodes that are part of coaxial concentric rings. The sensor consists of a high-potential, low-potential and grounded electrodes. A grounded electrode is located between the high-potential and low-potential electrodes, as well as around them.A simplified analytical calculation model for obtaining the analytical response characteristic of the change in the informative component of the sensor electric capacity on the course of the disk springs in the CA is presented. The reliability of the model and the response characteristics are confirmed experimentally by testing a laboratory prototype of a capacitive sensor.